The efficacy of removal of animal milk from the diet in functional dyspepsia: A cross-sectional study - Akpınar A.; Kochan K.; Kiremitci S.; Seven G.; İNCE A. T.; ŞENTÜRK H. (My University, 2024)
Background and study aims: We aimed to investigate the effect of removing milk and dairy products from diets on functional dyspepsia (FD) symptoms, as the aetiology remains unclear and new management approaches are needed. Patients and methods: This cross-sectional cohort study included 120 patients, with a mean age of 42.5 ± 12.3, of whom 77 (64.2 %) were female, with FD diagnosed by the Rome IV criteria. Patients were divided equally into two groups: those who eliminated milk and dairy products from their diet under the advice of a dietician without medical treatment and those who did not. The severity of symptoms was assessed using the gastrointestinal symptom rating scale (GSRS) at the beginning and end of a one-month period. Results: The restricted and unrestricted diet groups showed no significant differences in age, body mass index, symptom frequency and duration, weight changes, FD subtype, and gastroscopy results (p > 0.05). The diet group had more female patients (p = 0.01) and higher GSRS scores at the beginning (p = 0.01) but similar scores at the end of the study (p = 0.99). After one month, both groups had improved GSRS scores (p = 0.01), but the diet group had a more significant decrease in total symptom scores (p = 0.01) and in 7 of the 15 subsets (p < 0.05). Conclusion: Of the 120 FD patients who followed up for one month, 60 who removed milk products had a more significant reduction in GSRS symptom score and 7 of the 15 symptom subset scores than 60 patients receiving an unrestricted diet.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (Med); Gastroenteroloji Ve Hepatoloji; Klinik Tıp; Clinical Medicine (Med); Gastroenterology & Hepatology; Clinical Medicine; Gastroenteroloji; Gastroenterology; Dairy products; Functional dyspepsia; Gastrointestinal symptoms; Milk